(untitled) (Research, Society and Development, 2021)
TICs have been well accepted by elementary school students, but the teacher is not always prepared to encourage and build this type of work. Faced with the difficulty of living with the new language, questions are raised about the theoretical basis and strength of the video tool to encourage text production. Today we are experiencing an opportune moment since the reference document, the Common National Curriculum Base - BNCC - guides and recommends an interactionist teaching and the use of TDICs, in addition to another reinforcement, the pandemic, which incited the teaching staff of basic education to relearn digital technologies and the media in the area of Languages and their Technologies. The objective, therefore, is to suggest to teachers one more option / tool for teaching Portuguese Language in which they can work with high school classes focusing on the dissemination of indications of books made by the students themselves, videos that they produce in a way dynamic that brings interest and awakens the reading through the recommendations made. The research is based on the qualitative methodology, of bibliographic nature, with theoretical support in BNCC (2018), Rojo (2009;2012;2016;2019), Antunes (2003,2007), Ana Elisa Ribeiro (2007;2013), among others that discuss the theme. The dialogues produced between teachers should contribute to better and productive days in the classroom at the elementary school.